Nutritional, Antioxidant and Glycemic Response of Dark Chocolate Prepared with Sacha Inchi Oil - Halib, Hasmiza; Rozaimi, Nurul Syafiqah; Awi, Anis Sofiya; Taib, Nur Anis Syafiqah; Hussin, Napisah; Mhd Jalil, Abbe Maleyki; Saupi, Intan Anis (Jurnal Gizi dan Pangan, 2025)
This study aimed to enhance the nutritional and functional quality of dark chocolate by incorporating Sacha Inchi Oil (SIO), a healthier fat alternative derived from Plukenetia volubilis, which is rich in polyunsaturated fatty acids and antioxidants. The potential of SIO as a Cocoa Butter Equivalent (CBE) was evaluated in dark chocolate formulations containing 1%, 3%, and 5% SIO. Proximate composition and antioxidant capacity were analysed using standard methods (soxhlet, kjeldahl, total polyphenol content, total flavonoid content, 2,2-diphenyl-1-picrylhydrazyl (DPPH), and FRAP). Significant differences (p<0.05) were observed in fat, fiber, moisture, and energy contents, with the 5% SIO formulation showing reduced fat and energy levels, increased fiber and moisture, and the highest antioxidant activity. Additionally, a non-randomized controlled trial involving ten healthy participants was conducted to determine the Glycemic Index (GI) and Glycemic Load (GL) of the samples. While the control and 1% SIO samples exhibited high GI, the 3% and 5% SIO formulations were classified as medium GI, and all samples demonstrated low GL. The 5% SIO chocolate had the lowest glycemic response. These findings indicate that SIO can improve the nutritional profile, antioxidant properties, and glycemic response of dark chocolate, supporting its application as a functional ingredient in the development of healthier chocolate products, particularly for health-conscious populations in developing countries.